UMP to share on Publication of High Impact Journal - Siti Sarah, Mohamad Rajimi (2018)
Kuantan. 29 January – Publication Office of Universiti Malaysia Pahang has successfully organized a Journal Management Workshop: Towards SCOPUS and ISI Indexes. The workshop were attended by over than 30 journal editors from Malaysian Technical University Network (MTUN).